Tokopedia E-Commerce is Being Used to Present Opportunities for Young Business Owners to Succeed in the Digital Economy Amid the Pandemic - Greian April Pangilinan; Amirsyah Tambunan; Eka Dian Astuti (Pandawan Sejahtera Indonesia, 2023)
This study explores Tokopedia E-Commerce's role in providing young entrepreneurs with opportunities to succeed in the digital economy during the pandemic. The COVID-19 pandemic has significantly changed the landscape for business, with social restrictions and lockdowns becoming major challenges for many brick-and-mortar stores. In this context, e-commerce platforms like Tokopedia have become an attractive solution for young entrepreneurs who want to master the new challenges and opportunities of the digital age. The purpose of this study is to analyze how Tokopedia E-Commerce is providing opportunities for young entrepreneurs to overcome current economic challenges. The study takes a qualitative approach, gathering data through interviews and content analysis with business her owners using the Tokopedia platform. The results of this study show that Tokopedia E-Commerce is giving young entrepreneurs broad access to sell their products online, reach a wider audience and increase sales. In addition, we provide various functions and services to support business development, such as training and technical support. In the context of the COVID-19 pandemic, using Tokopedia E-commerce has helped young business owners survive and even thrive in difficult circumstances. The platform has opened up new opportunities to sell products online and reach a wider consumer base, reducing reliance on physically limited stores due to social restrictions. The study therefore concludes that Tokopedia E Commerce offers a significant opportunity for young entrepreneurs to succeed in the digital economy, especially in the current pandemic era. Using this platform, young entrepreneurs can overcome economic challenges and gain access to a wider market, thereby enhancing the sustainability and growth of their future business.